Routledge handbook of sport history - Phillips, Murray G.; Booth, Douglas; Adams, Carly (Routledge, Taylor & Francis Group, 2022)
"The Routledge Handbook of Sport History is a new and innovative survey of the discipline of sport history. Global in scope, it examines the key contemporary issues in sports historiography, sheds light on previously ignored topics, and sets an intellectual agenda for the future development of the discipline. The book explores both traditional and non-traditional methodologies in sport history, and traces the interface between sport history and other fields of research, such as literature, material culture and the digital humanities. It considers the importance of key issues such as gender, race, sexuality and politics to our understanding of sport history, and focuses on innovative ways that the scholarship around these issues is challenging accepted discourses. This is the first handbook to include a full section on indigenous sport history, a topic that has often been ignored in sport history surveys despite its powerful upstream influence on contemporary sport. The book also reflects carefully on the central importance of sport history journals in shaping the development of the discipline. This book is an essential reference for any student, researcher or scholar with an interest in sport history or the relationship between sport and society. It will also be fascinating reading for any historians looking for fresh perspectives on contemporary historiography or social and cultural history"
Keywords: Geschichte; Sport; Sports / History; Sports; History; Aufsatzsammlung